Religionsskiftet i sen vikingetid – Belyst ud fra Harvey Whitehouses teori om religiøse modaliteter - Geertz, Njal J. (Kuml, 2011)
The religious transition in the Late Viking Age examined on the basis of Harvey Whitehouse’s theory of religious modality The point of no return in the transition between pagan and Christian religious systems is pinpointed as the inscription on a rune stone erected between the two burial mounds at Jelling. Since the religious change did not take place exclusively in the Late Viking Age, the time frame of this article is restricted to before AD 1000. The main geographical area from which empirical data are available is loosely defined as that comprising present day Scandinavia and Northern Germany. The archaeological evidence employed by earlier scholars in examining the religious transition in this area falls mainly into three categories: burials, cult sites and the site of Jelling. The interpretation reached on the basis of these finds was that the transition from Paganism to Christianity occurred without conflict because the structure of the pagan cult was the same as that in the Christian Church. This interpretation appears somewhat unfounded in the archaeological record. By using Harvey Whitehouse’s theory of divergent modes of religiosity (DMR), the aim of this article is to gain a more detailed and consistent picture of the religious mode prior to the transition from Paganism to Christianity. In short, Harvey Whitehouse’s theory claims that all religiosity is either imagistic or doctrinal, depending on how the participants in various religions organise their rituals and how they create religious meaning. The imagistic mode is characterised by low frequency, high arousal (often violent) rituals where religious meaning is created by what Harvey Whitehouse calls spontaneous exegetical reflection. In combination, these activate the episodic memory when participating in religious activities. The participants in imagistic rituals often live in societies with a low degree of centralisation and often with weak or even no ritual leadership. This religious mode also has a small-scale and slow geographical spread because of the personal nature of the rituals. The doctrinal mode is characterised by high-frequency rituals with low arousal, where religious meaning is taught by logical, integrated narratives. In combination, these activate the semantic memory when participating in such rituals. This mode is found in societies with a high degree of centralisation and is carried by a strong religious leadership, making a large-scale and rapid spread possible. The DMR theory has 12 defining variables which have opposing qualities depending on the modality distinguishable in the archaeological record. The idea is to apply the DMR theory to selected archaeological sources consisting of the following find categories: burials, burial sites, central places and monumental burials. The first find category discussed is the burials and burial sites of the Late Viking Age. This category contains much information relevant to several variables in DMR. When specific combinations of weapons and equestrian grave goods, and special grave constructions, are considered, the evidence seems to suggest that, on a regional level, there are clear similarities between these types of burials, corresponding to the doctrinal modality. Based on an interpretation of similarities existing over a significant time period, it is assumed that a control of the narrative underlines the ritual objects employed. In contrast, the burial sites described in the case studies from the Late Viking Age seem to reflect a hierarchical organization of the burial sites and a distribution of the overall number of grave goods in the graves which shows traits resembling imagistic modality. Since the latter sites show a segmented heterogeneous distribution of grave goods, they are interpreted as an expression of a small-scale, exclusive religious burial system. This is also reflected in the gender and age distribution of the skeletal remains with a secure dating to the Late Viking Age. The material here clearly shows that a large proportion of the living population was denied access to the burial sites, and since almost all skeletal remains were found on burial sites, this is interpreted as corresponding to imagistic modality for the society as a whole. The central places are relevant because it is here we find the remains of cult buildings from the periods leading up to the Viking Age. The archaeological record reveals that there were specific buildings where different rituals were performed over a considerable period of time. The various objects found in the buildings, such as bracteates, gold foil figures and drinking vessels, are mentioned in the context of their religious interpretation. The conclusion reached is that the objects seem to undergo a degree of formalisation towards a more abstract expression, which I claim is based on a greater dependency on narratives in understanding and recognising the images depicted on the objects. This dependency on religious narratives corresponds to the doctrinal modality. On the other hand, the fact that these central places had such long periods of activity, and that they are located within the chieftains’ farmsteads, seems to indicate that the rituals performed within the buildings were not “public” in a broad sense, but were generally exclusive and thus an imagistic trait. The final archaeological source comprises the monumental long-ship burials dating from the Late Viking Age. An interpretation proposed by Tejrne Gansum, based on the evidence from the long-ship burial at Oseberg in Norway, claims that these burials were constructed as public events, where significant sacrifices of valuables, livestock and even people were performed on the ship like on the stage of a theatre. These burials are considered to be violent and to represent events which quite easily could activate episodic memory; they are therefore considered to be manifestations of imagistic modality. The two foreign written sources, the chronicle of Adam of Bremen and the travel accounts of Ibn Fadlan, were chosen because much of the information they contain can be verified by the archaeological record. Adam of Bremen’s account confirms that there were specific buildings where the cult and rituals were performed. The specific drinking and sacrificial rituals described in the text also correspond to evidence in the archaeological record. It is also noted that the frequency of these rituals was very low. In Ibn Fadlan’s travelogue, a supposed Viking ship burial is described. This source provides a large amount of information, not all of which, however, can be confirmed by the archaeological record. The verifiable information shows that the choice of sacrificial objects and the drinking rituals were consistent with Adam of Bremen’s chronicle. Apart from these observations, it is also noted that the spectators were not given specific information by the participants in the ritual, yet they still knew which actions were taking place inside the tent erected on the ship. What is described here seems to fit with imagistic modality. The conclusion reached in this article is that the structure of the pre-Christian religion was not identical to that of the Christian religion, but that there were significant similarities. These similarities are due to the fact that the nobility of the pre-Christian period made great use of religious narrative and were therefore accustomed to control and strong religious leadership indicative of doctrinal modality. The peaceful shift in religion is most likely due to the circumstance that it was the same nobility that erected cult houses in the Viking Age which were also responsible for the construction and ownership of the first wooden churches. Their willingness to change must have been based on personal sympathies towards the Christian message. Njal J. Geertz Ringkøbing-Skjern Museum